Effect of Treatment with Cryopreserved Fetal Neuronal Cells on Prooxidant-Antioxidant Balance in Rats with Experimental Cranio-Skeletal Injury - Borys, Roman M.; Gozhenko, Anatoliy I.; Goltsev, Anatoliy N. (Problems of Cryobiology and Cryomedicine, 2014)
In the response to cranio-skeletal injury, complicated by bleeding, the content of primary and secondary products of lipid peroxidation (LPO) in liver homogenate significantly increased, and achieved a maximum level to the 14th day of the experiment and was significantly higher than the control level during 25 days of observation. Within the 3rd–14th days the accumulation of LPO products occured on the background of significant decrease of superoxide dismutase (SOD) activity, without any changes in catalase activity and compensatory increase of ceruloplasmin content to the 3rd day of the experiment. From 14th to 25th day following treatment with cryopreserved fetal neuronal cells we observed less pronounced deviations of lipid peroxidation in terms of content of primary LPO products (diene conjugates), and content of secondary LPO products (TBA-active) from the 3rd to 7th day. Catalase content was reduced through the 3rd–14th days of the experiment, increased by the 25th day; from the 14th day we observed a protective effect of cryopreserved fetal neuronal cells in terms of SOD activity. There was virtually no correcting effect found in blood serum ceruloplasmin content. Probl Cryobiol Cryomed 2014; 24(1):67–74.